Rethinking Urban Risk and Resettlement in the Global South - Johnson, Cassidy; Jain, Garima; Lavell, Allan (UCL Press, 2021)
Environmental changes have significant impacts on people's lives and livelihoods, particularly the urban poor and those living in informal settlements. In an effort to reduce urban residents' exposure to climate change and hazards such as natural disasters, resettlement programmes are becoming widespread across the Global South. While resettlement may reduce a region's future climate-related disaster risk, it often increases poverty and vulnerability, and can be used as a reason to evict people from areas undergoing redevelopment. A collaboration between the Bartlett Development Planning Unit at UCL, the Indian Institute for Human Settlements and the Latin American Social Science Faculty, Rethinking Urban Risk and Resettlement in the Global South collates the findings from 'Reducing Relocation Risks', a research project that studied urban areas across India, Uganda, Peru, Colombia and Mexico. The findings are augmented with chapters by researchers with many years of insight into resettlement, property rights and evictions, who offer cases from Monserrat, Cambodia, Philippines and elsewhere. The contributors collectively argue that the processes for making and implementing decisions play a large part in determining whether outcomes are socially just, and examine various value systems and strategies adopted by individuals versus authorities. Considering perceptions of risk, the volume offers a unique way to think about economic assessments in the context of resettlement and draws parallels between different country contexts to compare fully urbanised areas with those experiencing urban growth. It also provides an opportunity to re-think how disaster risk management can better address the accumulation of urban risks through urban planning.